Profile of Skin Biopsy Patients in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia - Wandhita, R.A. Astrid Putri; Sandhika, Willy; Listiawan, M. Yulianto (Folia Medica Indonesiana, 2022)
Highlight: • Profile of skin biopsy results which carried out the anatomical pathology examination was reviewed. • The highest skin biopsy disease group case are erythropapulosquamous, infection, skin tumor, vesiculobullous, connective tissue disease, pigmentation disorders, and vasculitis Abstract: Skin biopsy is an important tool used by dermatologists in diagnostic determination. The correlation between clinical and histological features is needed in understanding pathogenesis and formulating the diagnosis of a skin disease with a greatly varied spectrum of histopathological results, while the observable clinical symptoms are highly limited. Skin diseases are still a serious problem worldwide, especially in Indonesia. Based on the Indonesian Health Profile in 2010, skin diseases ranked third out of 10 most diseases in outpatients in hospitals throughout Indonesia. This study was a review of the profile of skin biopsy results in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia from 1 July 2014 to 31 July 2019, which were subjected to anatomic pathology examination. This study was an observational descriptive study using secondary data sources from the medical records at the Communication and Information Technology Installation (ICT) of Dr. Soetomo General Academic Hospital, Surabaya. Based on data searches, the total number of biopsy examinations performed was 1,368 cases. There were more female patients (50.3%) than males (49.7%). The most common skin disorder found was erythropapulosquamous disorder (30%), followed by infection (18%). Other cases consisted of skin tumor (15%), vesiculobullous (13%), connective tissue disease (7%), pigmentation disorders (5%), and vasculitis (5%). Diseases that could not be classified into 7 groups of the biopsy criteria were grouped separately in other diseases (7%).